Edukasi Kesehatan Kognitif sebagai Upaya Meningkatkan Kesadaran Lansia dalam Menjaga Fungsi Kognitif pada Peserta Sekolah Lansia Indonesia Ramah Lansia Jawa Barat (IRL Jabar) - Virda Rahmatunnisa; Susiana Nugraha; Laila Ulfa; Yuna Trisuci Aprillia; Gita Trikartika; Siyamto Siyamto (Universitas Respati Indonesia, 2026)
Background: Population ageing has increased the prevalence of cognitive decline among older adults. Cognitive impairment affects memory, thinking, communication, decision-making, and independence in daily activities. Limited knowledge regarding brain health highlights the need for community-based health education. Elderly schools provide an appropriate setting to promote healthy ageing through continuous learning and empowerment. Objective: This community service program aimed to improve older adults' knowledge and awareness regarding cognitive health among participants of the Indonesia Ramah Lansia Elderly School, West Java. Methods: The program applied a participatory health promotion approach through interactive lectures, discussions, question-and-answer sessions, cognitive stimulation demonstrations, and educational games. Educational materials included cognitive function, risk factors for cognitive decline, early signs of cognitive impairment, and strategies to maintain brain health through physical activity, mental stimulation, balanced nutrition, adequate sleep, and social engagement. Results: Participants actively engaged in all educational activities and demonstrated improved understanding of cognitive health. They were able to identify practical activities to maintain brain function and expressed greater awareness of adopting healthy lifestyles to support cognitive wellbeing. Conclusion: Cognitive health education is an effective health promotion strategy to improve older adults' knowledge and awareness regarding cognitive function. Sustainable educational programs through elderly schools are recommended to support healthy ageing and maintain independence among older adults